Hollow structures with rare earths: Synthesis and electrocatalytic applications. Issue 5 (September 2022) - Guo, Linchuan; Mu, Zhaori; Da, Pengfei; Weng, Zheng; Xi, Pinxian; Yan, Chun-Hua
Abstract: Electrochemical conversion is an eco-friendly and controllable way to achieve sustainable use of energy. An enhanced energy conversion efficiency requires efficient electrocatalysts to reduce the electrochemical energy barrier. The hollow structures, which have the advantage of optimizing mass/charge transfer, provide a platform for full contact between the electrocatalysts and the reactants, which has great potential for advanced electrocatalysts. In addition, rare earth-based materials integrate unique electronic configuration and chemical behavior into electrocatalysts, leading to improved performance and selectivity for various electrocatalysis. Combining hollow structures with rare earths is fascinating and challenging in terms of synthesis and electrocatalysis. This review expounds general synthesis methods of hollow structures with rare earths and then summarizes strategies to prepare highly efficient hollow electrocatalysts with rare earths. Highlights: Hollow structure endows materials with many advantages and is one of common means to improve catalytic performance. The composition and structure of hollow materials have been diversified with the development of synthesis methods. The rare earths have great potential in electrocatalysis because of its special electronic configuration. Ceria-based materials and perovskite-type rare earth oxides are regarded as efficient and worthy electrocatalysts. Some particularities of rare earths need to be discussed, including the tendencies shown in the synthesis process and the hollowing strategies for common rare earths-based electrocatalysts.